Materials, skills and gender identities: men, women and home improvement practices in New Zealand. Issue 4 (2nd April 2016) - Cox, Rosie
Abstract : The article explores the interactions of materials, skills and gender identity through examining DIY practices in New Zealand. It traces the relationship between materials used for home repairs, the competences needed to use them and the (re)production of specific gendered identities. It argues that housing and building materials were an important part of the European settler history of the country and this history forms the context within which New Zealanders work on their houses today. Drawing on interviews with 30 Pākehā homeowners, it explores how both men and women respond to the materials of their homes, how skills are acquired in relation to the demands of the materials used and how these skills become part of the (re)production of specific white, heterosexual gender identities. The figure of the 'Kiwi bloke' is discussed as an important imaginary in the negotiation of gender identities for both men and women. Interviewees saw their DIY activities in the light of the creation and re-creation of this specific national and gendered identity. The article reveals the intertwining of history and materiality in the continual negotiation and contestation of gendered identities.